2023
DOI: 10.1126/sciadv.adi7337
|View full text |Cite
|
Sign up to set email alerts
|

Lachnospiraceae -derived butyrate mediates protection of high fermentable fiber against placental inflammation in gestational diabetes mellitus

Shuangbo Huang,
Jianzhao Chen,
Zhijuan Cui
et al.

Abstract: Inflammation-associated insulin resistance is a key trigger of gestational diabetes mellitus (GDM), but the underlying mechanisms and effective interventions remain unclear. Here, we report the association of placental inflammation (tumor necrosis factor–α) and abnormal maternal glucose metabolism in patients with GDM, and a high fermentable dietary fiber (HFDF; konjac ) could reduce GDM development through gut flora–short-chain fatty acid–placental inflammation axis in GDM mouse model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…37 Additionally, inflammation-driven insulin resistance was shown to play a crucial role in GDM, with high fermentable dietary fiber (HFDF) reducing GDM development in mice by modulating the gut flora–short-chain fatty acid–placental inflammation axis. 38 In line with these findings, our study also indicated that inadequate dietary fiber intake increased the risk of GDM. This correlation remained significant even after adjusting for maternal age and pre-pregnancy BMI in the control group.…”
Section: Discussionsupporting
confidence: 87%
“…37 Additionally, inflammation-driven insulin resistance was shown to play a crucial role in GDM, with high fermentable dietary fiber (HFDF) reducing GDM development in mice by modulating the gut flora–short-chain fatty acid–placental inflammation axis. 38 In line with these findings, our study also indicated that inadequate dietary fiber intake increased the risk of GDM. This correlation remained significant even after adjusting for maternal age and pre-pregnancy BMI in the control group.…”
Section: Discussionsupporting
confidence: 87%
“…The placenta is a key bridge between mother and fetus and plays an important role in fetal development ( Hu et al., 2021 ). Reduced insulin sensitivity is associated with trophoblast invasion and angiogenesis impairment, resulting in reduction of reproductive efficiency, with further adverse effects on fetal outcomes, such as high stillbirth rates and low birth weight ( Huang et al., 2023 ; Martino et al., 2016 ; Tan et al., 2016 ; Tanaka et al., 2018 ; Yang et al., 2021b ). A richer vascular system could efficiently transport oxygen and nutrients from mother to fetus, thus increasing the vitality of piglets ( Huang et al., 2021a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang et al. found that high dietary fiber, which increased abundances of Lachnospiraceae and butyrate, enhanced the gut barrier and inhibited the transfer of LPS, thus reducing placental inflammation and insulin resistance ( 246 ). Similar results were also found in pigs.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%